A NEW PROTOTYPE IN CLASSICAL TURKISH LITERATURE: THE RIGHTEOUS INTELLECTUAL PROTOTYPE - Dalyan, Ayse (Selcuk Univ, Inst Turkish Studies, 2016)
In Manzume, the quasida of Herzegovinian Arif Hikmet, who is a poet in Encume-i Suara in XIXth century, the statement on the people ruling the government as being untrustworthy is being emphasized. With this a society not trusting the statesmen and cloistering itself in a climate of distrust is the subject in this text. The failures the state has experienced and the fixation of the statesmen to the joys of the world have made the people from that period unhappy and have directed them to question life, government and humanity. In this process the human being, living under the pressure of the authoritarian government, has now opened his eyes and is able to see the problems harming the governemnt. In fact, the main reason for the unhappiness of the human being trying to be individualized is mismanagement, so the collapsing government. So the text is representing the collapse of the Ottoman Empire. The representative human in the qasida plays a part in the text with his effort on being transformed from a slave into an individual. An individual being tradition-bound and being not able to transform completely at the same time is encountered. The ideal person presented by the poet develops by changing with the rind type of the tradition in accordance with the period. It is understood from the text that the individual is observing the world and is trying to comment on it. In this sense the individual is literally in the middle of a chaos. For this reason the new prototype is unhappy. It is mentioned in the text that the righteous people trying to be individualized are unhappy. So with the new person presented in the text the Righteous Intellectual Prototype is being pointed out. The study consists of two parts. In the first part traces about the ideal person model of the period have been determined through the unit of meaning under the title. Structure.. In the second part, the aim was to reach a culture interpretation by entreating a poem in the light of gathered information from the. structure., in accordance with a method emphasizing the determination of the ideal prototype of the period.
Keywords: Herzegovinian Arif Hikmet; quasida; righteous intellectual prototype; ghettoness; change